Optimal service restoration in active distribution networks considering microgrid formation and voltage control devices - Macedo, Leonardo H. (2021)
This paper presents a new mixed-integer linear programming model for the optimal restoration of active distribution networks during permanent fault events considering not only network reconfiguration but also the islanded operation of distributed generation, thereby giving rise to the formation of microgrids. To that end, the proposed approach accounts for both the black-start capacity of generators and the connection of multiple generators to the same microgrid. Moreover, voltage control devices such as substations on-load tap changers, voltage regulators, and capacitor banks are also considered in the formulation. The model is driven by the minimization of the out-of-service load after single or multiple faults in the network using the minimum number of switching operations and modifications in the statuses of the voltage control devices. The proposed model is implemented in the mathematical modeling language AMPL and solved with the CPLEX solver. Tests are conducted using a 53-node distribution system considering different fault locations. Numerical results show the relevant effect of microgrid formation and voltage control in the restoration process. Simulations also prove the effective performance of the proposed approach in terms of computation time.